Using patient experience data to develop a patient experience toolkit to improve hospital care: a mixed-methods study - Laura Sheard; Claire Marsh; Thomas Mills; Rosemary Peacock; Joseph Langley; Rebecca Partridge; Ian Gwilt; Rebecca Lawton (National Institute for Health Research, 2019)
Background: Patients are increasingly being asked to provide feedback about their experience of health-care services. Within the NHS, a significant level of resource is now allocated to the collection of this feedback. However, it is not well understood whether or not, or how, health-care staff are able to use these data to make improvements to future care delivery. Objective: To understand and enhance how hospital staff learn from and act on patient experience (PE) feedback in order to co-design, test, refine and evaluate a Patient Experience Toolkit (PET). Design: A predominantly qualitative study with four interlinking work packages. Setting: Three NHS trusts in the north of England, focusing on six ward-based clinical teams (two at each trust). Methods: A scoping review and qualitative exploratory study were conducted between November 2015 and August 2016. The findings of this work fed into a participatory co-design process with ward staff and patient representatives, which led to the production of the PET. This was primarily based on activities undertaken in three workshops (over the winter of 2016/17). Then, the facilitated use of the PET took place across the six wards over a 12-month period (February 2017 to February 2018). This involved testing and refinement through an action research (AR) methodology. A large, mixed-methods, independent process evaluation was conducted over the same 12-month period. Findings: The testing and refinement of the PET during the AR phase, with the mixed-methods evaluation running alongside it, produced noteworthy findings. The idea that current PE data can be effectively triangulated for the purpose of improvement is largely a fallacy. Rather, additional but more relational feedback had to be collected by patient representatives, an unanticipated element of the study, to provide health-care staff with data that they could work with more easily. Multidisciplinary involvement in PE initiatives is difficult to establish unless teams already work in this way. Regardless, there is merit in involving different levels of the nursing hierarchy. Consideration of patient feedback by health-care staff can be an emotive process that may be difficult initially and that needs dedicated time and sensitive management. The six ward teams engaged variably with the AR process over a 12-month period. Some teams implemented far-reaching plans, whereas other teams focused on time-minimising 'quick wins'. The evaluation found that facilitation of the toolkit was central to its implementation. The most important factors here were the development of relationships between people and the facilitator's ability to navigate organisational complexity. Limitations: The settings in which the PET was tested were extremely diverse, so the influence of variable context limits hard conclusions about its success. Conclusions: The current manner in which PE feedback is collected and used is generally not fit for the purpose of enabling health-care staff to make meaningful local improvements. The PET was co-designed with health-care staff and patient representatives but it requires skilled facilitation to achieve successful outcomes. Funding: The National Institute for Health Research Health Services and Delivery Research programme.